PERJANJIAN BELI SEWA SEBAGAI PERJANJIAN BAKU - Siti Nurhasanah (Universitas Lampung, 2007)
Legal status of the parties to the agreement to buy rental car as standard contracts, showing the rights and obligations that are not balanced between sellers and buyers lease rent. The obligation to lease buyers, more dominant than the rights that should be owned. This happened contrary to the rights and obligations for employers. Keywords: Buy Lease, Raw Agreements